Use Of Papaya Fruit (Carica Papaya L) As A Stunting Prevention Effort - Fatmawati, Nurul; Yesvi Zulfiana; Sri Handayani (Journal for Quality in Public Health, 2023)
According to WHO, the prevalence of short toddlers becomes a public health problem if the prevalence is 20% or more. From the PSG results data in 2017, the prevalence of stunting in NTB Province was 37.2% higher than the national average of 29.6%. , 29 %. For the highest stunting prevalence in Sumbawa Regency, which is 41.9%, followed by Central Lombok 39.9%, Dompu 38.3%, Mataram City 37.8%, North Lombok 37.6%, Bima 36.6%, Bima City 36 .3%, West Lombok 36.1% and East Lombok 35.1%. The method used in this study is quantitative, which is to find out an accurate picture of the utilization or use of papaya fruit (Carica Papaya L). The population in this study were mothers who had children aged 1 -5 years. In this study, it can be concluded that most of the mothers under five have used papaya fruit (Carica Papaya L) as a stunting prevention. Based on the results of the study it can be concluded that most of the sex of toddlers is male by 56 (54%) and most of the mothers of toddlers have used papaya fruit by 77 (54%). In 100 grams of papaya fruit contains 450 milligrams, vitamin A, 74 milligrams of vitamin C, 86.6 grams of water, 0.5 grams of protein and 0.7 grams of fiber. The content contained in papaya fruit can increase appetite in toddlers so that it affects weight gain.